Unholy Alliance: Nationalism, Communalism, and the 2024 Anti-Hindu Violence in Bangladesh - Paul, Anurag (FISIP UIN Sunan Gunung Djati Bandung, 2025)
Research Problem: Bangladesh’s struggle with national identity has long been shaped by competing ideological forces between secular nationalism and religious conservatism. In recent years, this tension has manifested in sectarian violence targeting minority groups, particularly Hindus. The issue is compounded by media representations that amplify exclusionary nationalist discourses and normalize intolerance. The 2024 student–citizen protests, which escalated into widespread violence, exposed how nationalist rhetoric, cultural chauvinism, and political rivalry undermine the nation’s pluralistic ideals. The central research problem lies in understanding how political discourse and media narratives interact to reinforce exclusionary nationalism and marginalize minority communities within the framework of Bangladesh’s postcolonial identity. Research Purposes: This study aims to examine the interplay between media narratives, nationalist ideologies, and sectarian violence in Bangladesh. Specifically, it seeks to: (1) analyze how exclusionary nationalism is constructed and legitimized through media and political discourse; (2) explore the ideological roots of minority marginalization in Bangladesh’s post-independence history; and (3) contextualize Bangladesh’s experience within broader global trends of religious nationalism. Ultimately, the study intends to offer a critical reflection on the paradox of nationalism—how the idea of unity and sovereignty can simultaneously generate exclusion and conflict. Research Methods: The research employs a qualitative, interpretive approach, utilizing critical discourse analysis (CDA) to examine media coverage, political speeches, and public statements during the 2024 protests. A historical and ideological review supports the analysis, tracing the evolution of nationalist narratives since independence and assessing how they intersect with religious identity politics. Comparative insights from other contexts of sectarian nationalism are incorporated to highlight transnational parallels and to situate Bangladesh’s experience within a global framework of religious and political intolerance. Results and Discussion: Findings reveal that media representations and political rhetoric jointly contribute to constructing exclusionary forms of nationalism that portray minorities as external to the national identity. The Awami League’s secular project has been compromised by political pragmatism, while the BNP’s reliance on Islamic symbolism has deepened sectarian divisions. The 2024 protests exemplify how nationalist fervor and media sensationalism can converge to justify or obscure violence against minorities. The discourse of “national unity” is paradoxically used to silence diversity, exposing a deep crisis in Bangladesh’s vision of citizenship and belonging. The study highlights that religious nationalism, fueled by media narratives, perpetuates structural marginalization and undermines democratic pluralism. Research Implications and Contributions: This study contributes to a deeper understanding of how media and politics shape exclusionary nationalism in postcolonial states. Theoretically, it enriches scholarship on discourse, nationalism, and identity politics by showing how nationalist rhetoric in Bangladesh mirrors global patterns of intolerance. Practically, it underscores the urgent need for media accountability, inclusive policy reform, and civic education to counter extremist narratives. By drawing a parallel with post-Holocaust Germany’s reconciliation and nation-building, the paper offers a hopeful vision: Bangladesh, too, can move toward a more inclusive and pluralistic national identity, provided it is guided by enlightened leadership and supported by international solidarity.